Historical genesis of the concept of number and number systems - possibilities of application in the initial teaching of mathematics (II): Introduction, History of mathematics and teaching mathematics, Possibilities of applying the "history" of numbers in the teaching of mathematics, Examples of tasks, Conclusion, References - Gordić, Snežana; Lazić, Bojan; Milošević, Marina (Norma, 2022)
The history of mathematics and its discoveries have a significant role in the modern teaching of mathematics because they increase the motivation and interest of students in the subject. This paper aims to consider the possibilities of its application in practice based on a brief overview of existing research on the use of the history of mathematics in mathematics teaching. Examples of tasks related to the history of natural numbers and number systems that can be applied in the initial teaching of mathematics are presented. In the conclusion of the paper, an overview of number systems through history is summarized (Part I, NORMA XXVII, 1/2022), with special reference to the importance of positional number system, i.e. the advantages of the Indo-Arabic system, with recommendations for introducing these contents in elementary mathematics.
Keywords: history of mathematics; number systems; tasks; class teaching of mathematics